Uncovering small town secrets - Snell, Tyler Anne (Snell, Tyler Anne. Saving Kelby Creek series., 2021)
Alabama Detective Foster Lovett ignores his fellow deputies and takes on the investigation of his neighbor Millie Dean's missing brother.